2004
DOI: 10.1074/jbc.m405853200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Knockdown of the RNA-binding Protein CRD-BP Promotes Cell Proliferation via an Insulin-like Growth Factor II-dependent Pathway in Human K562 Leukemia Cells

Abstract: The c-myc mRNA coding region determinant-binding protein (CRD-BP) was first identified as a masking protein that stabilizes c-myc mRNA in a cell-free mRNA degradation system. Thus, CRD-BP is thought to promote cell proliferation by maintaining c-Myc at critical levels. CRD-BP also appears to be an oncofetal protein, based upon its expression during mammalian development and in some tumors. By using K562 leukemia cells as a model, we show that CRD-BP gene silencing by RNA interference significantly promoted pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 58 publications
(53 reference statements)
5
73
1
Order By: Relevance
“…Previous studies revealed that IMP1 knockdown in mammary adenocarcinoma-derived MCF-7 cells resulted in reduced proliferation correlating with decreased steady state levels of c-MYC (Ioannidis et al, 2005). In contrast, the knockdown of IMP1 caused increased proliferation correlating with elevated IGF-II protein levels in K562 leukemia cells (Liao et al, 2004). In agreement with studies performed in MCF-7 cells, IMP1 knockdown in ovarian carcinoma-derived ES-2 induced decreased proliferation starting 72 h after the transfection of siRNAs.…”
supporting
confidence: 81%
“…Previous studies revealed that IMP1 knockdown in mammary adenocarcinoma-derived MCF-7 cells resulted in reduced proliferation correlating with decreased steady state levels of c-MYC (Ioannidis et al, 2005). In contrast, the knockdown of IMP1 caused increased proliferation correlating with elevated IGF-II protein levels in K562 leukemia cells (Liao et al, 2004). In agreement with studies performed in MCF-7 cells, IMP1 knockdown in ovarian carcinoma-derived ES-2 induced decreased proliferation starting 72 h after the transfection of siRNAs.…”
supporting
confidence: 81%
“…S3). Of note, manipulation of IGF2BP1 in K562 erythroleukemia cells similarly had only minor effects on those genes (26). Following these initial studies, the potential for IGF2BP1-OE to regulate the expression levels of the let-7 miRNAs or LIN28 in adult CD34(+) erythroblasts via a feedback loop was investigated.…”
Section: Igf2bp1 Overexpression Reverses Adult Erythroblasts To a Mormentioning
confidence: 99%
“…Re-activation or elevated expression of the ZBP1 gene has been detected in mammalian tumors of different origins and has been considered a feature marker of clinical samples (Gu et al, 2004;Ioannidis et al, 2005;Yisraeli, 2005). A number of studies have revealed the positive or negative involvement of ZBP1 in tumorigenesis and tumor progression, including cancer cell proliferation, invasion and metastasis (Liao et al, 2004;Ross et al, 2001;Tessier et al, 2004;Wang et al, 2004). Substantial evidence implicates the role of ZBP1 in breast cancer invasiveness.…”
Section: Introductionmentioning
confidence: 99%